An ecological approach to understanding and addressing health inequities of systemic lupus erythematosus. (April 2023) - Reid, Mallet R; Danguecan, Ashley N; Colindres, Isabella; Witherspoon, Denasja; Rubinstein, Tamar B; Drenkard, Cristina; Knight, Andrea M; Cunningham, Natoshia R
Systemic Lupus Erythematosus (SLE) is a complex chronic autoimmune disease disproportionally afflicting women and, in particular, American Indian/Alaska Native, Black, and Hispanic women. These groups of women have significantly worse SLE-related health outcomes which are partially attributable to their exposure to marginalizing and interconnecting social issues like racism, sexism, economic inequality, and more. Although these groups of women have higher rates of SLE and though it is well known that they are at risk of exposure to marginalizing social phenomena, relatively little SLE literature explicitly links and addresses the relationship between marginalizing social issues and poor SLE-health outcomes among these women. Therefore, we developed a community-engaged partnership with two childhood-SLE diagnosed women of color to identify their perspectives on which systemic issues impacted on their SLE health-related outcomes. Afterward, we used Cochrane guidelines to conduct a rapid review associated with these identified issues and original SLE research. Then, we adapted an ecological model to illustrate the connection between systems issues and SLE health outcomes. Finally, we provided recommendations for ways to research and clinically mitigate SLE health inequities.